An empirical model for predicting the length of a capillary tube. Issue 5 (26th February 2021) - Freegah, Basim; Saleh, Qasim; Theeb, Maathe A.
Abstract: Any refrigerant device consists of several parts, and one of the most significant parts is the expansion device. This expansion device can be classified into several types according to the size of the refrigeration system. The capillary tube is used usually with a small refrigerant system size to reduce the higher pressure in the condenser into the low pressure in the evaporator. In this study, the effect of the capillary tube's diameter and that of the temperature of the condenser and evaporator on the length of such a device has been theoretically studied. Furthermore, a validation between the theoretical analysis and experimental findings from the literature review has been carried out. To achieve the theoretical aspect, MATLAB code has been developed. The results showed that the maximum difference between the theoretical and experimental results regarding temperature and pressure refrigeration is around 5% and 3.4%, respectively. Also, the results depict that the inner diameter and the condenser temperature have an effect on the length of the capillary tube. However, the effect of the inner diameter is higher compared with the condenser temperature. In addition, an equation to predict the length of the capillary tube has been developed with an accuracy of 98%. This equation is created as a function of the capillary tube's diameter and the temperature of the condenser and the evaporator. Moreover, this equation can be used to predict the length of the capillary tube for small refrigeration devices, especially those operating under 10 KW. The findings of this study can help make a mathematical approach used for the design of the capillary tube simpler and easier to apply.